2009
DOI: 10.1080/09720073.2009.11891087
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Jenukuruba Tribal Children in Mysore District, Karnataka

Abstract: A cross-sectional study was undertaken on 135 Jenukuruba tribal children belonging to 6+ to 10+ age group through purposive sampling method. Anthropometric measurements and Clinical observation techniques were used to analyse the nutritional status. Assessment of nutritional status using WHO recommended anthropometric indicator and Z-score interpretation revealed, high prevalence of mild (41.5%) and severe (6.7%) stunting, more prevalence of mild (40%) and severe (3.7%) in wasting, and underweight was 45.2% mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
3
1
Order By: Relevance
“…[35] The rates of underweight and stunting in the present study were higher than those in Lodha [25] and Santal [19] children from West Bengal. Moreover, the prevalence of wasting was lower than that in Santal [19] children and comparable to Lodha [25] children, indicating that the children in both communities were experiencing acute undernutrition.…”
Section: Discussioncontrasting
confidence: 80%
“…[35] The rates of underweight and stunting in the present study were higher than those in Lodha [25] and Santal [19] children from West Bengal. Moreover, the prevalence of wasting was lower than that in Santal [19] children and comparable to Lodha [25] children, indicating that the children in both communities were experiencing acute undernutrition.…”
Section: Discussioncontrasting
confidence: 80%
“…[9,17,11] Similar prevalence of malnutrition is reported from a study done among Jenukuruba tribal children reported 45.2% of children as having moderate underweight and 14.8% as having severe underweight. [18] Another study in the villages of Dharwad and Haliyal taluks reported 44.4% of children as underweight, [19] which is similar to the present study. Similar higher prevalence of 59.9% was reported among tea garden population of Assam.…”
Section: Resultssupporting
confidence: 82%
“…In rural (11 %) and urban blocks (6%) easy pluckability was observed in children of Kangra and Kullu Districts respectively. Prabhakar and Gangadhar (2009) reported that majority of the children had lack of lustre (94.1%), sparseness (94.1%) and straightness (83%) in hair.…”
Section: Nutrient Intakementioning
confidence: 99%